Evaluación del caso de negocio para un piloto de bombeo electrosumergible con motor de imanes permanentes (PMM) para la reducción de consumo energético y el aumento de la eficiencia en un campo de Ecopetrol (2019)
In this grade work a business case was carried out to allow us to look at the viability by implementing permanent magnet motors in electro-submersible pumping equipment. Previous cases developed by different companies will be taken into account and the development of our own analysis emphasized in energy saving and motor efficiency through simulations and performance curve analysis. Based on the results, a conservative energy saving value was established to economically analyze with sensitivity the profitability of this technology by implementing it, in a single well and a drilling campaign.